2015
DOI: 10.5530/pc.2015.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intestinal Morphology of Rats Fed with Different Levels of Bee Pollen

Abstract: Context: Bee pollen has been related to therapeutic properties including antibiotic, antineoplasic, antidiarrhoeic and antioxidant activities. However, little is known about the effect of pollen feeding on the intestinal structures and functions. Aims: The objective of this study was to evaluate the small intestine morphology in rats fed with three different pollen levels. Materials and Methods: Forty rats were randomly separated into 4 groups of 10 rats each. Control group (C) was fed with a basic diet, group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Moreover, crypts depth was significantly deeper in the Pr group. These results are consistent with another study [ 50 ], and confirm the positive effect of dietary propolis supplementation on the intestinal morphology and mucosal development. Therefore, the overall histomorphometric changes induced by propolis could be remarkably useful, particularly during heat stress, when the intestinal mucosa is damaged and requires a rapid renewal of villus cells [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, crypts depth was significantly deeper in the Pr group. These results are consistent with another study [ 50 ], and confirm the positive effect of dietary propolis supplementation on the intestinal morphology and mucosal development. Therefore, the overall histomorphometric changes induced by propolis could be remarkably useful, particularly during heat stress, when the intestinal mucosa is damaged and requires a rapid renewal of villus cells [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…The small intestine is an important organ responsible for the digestion and absorption of nutrients from the diet. Any changes in its function affect the function of other organs and systems in the organism [15]. There are only a few studies that have previously evaluated the effect of propolis and bee pollen on the intestinal morphology of broiler chickens, and their results are contradictory [12,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…One reason could be the stimulation of digestive enzymes by HBPE, which are essential factors in the digestion and absorption of nutrients. Stimulation of digestive enzymes and the modulating digestive organ by HBPE have been reported in other animals (Abdelnour et al, 2019; Fazayeli‐Rad, Afzali, Farhangfar, & Asghari, 2015; Toman, Hajkova, & Hluchy, 2015; Wang, Li, Wang, Xin, & Wang, 2007). In our previous studies, we observed that garlic ( Allium sativum ) (Esmaeili et al., 2017a) and barberry root extract (Ramezanzadeh, Abedian Kenari, Esmaeili, & Rombenso, 2020) could stimulate digestive enzymes.…”
Section: Discussionmentioning
confidence: 69%